Financial distress condition of indonesian aviation sector companies before and during the Covid-19 pandemic - Desiana Rahmawati; Adipura Danang Maulana (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2023)
This study examines differences in financial distress conditions based on the Altman, Grover, and Springate models before and during the Covid-19 pandemic. The research design used is inferential research with a quantitative approach. The data used is quantitative in the form of financial statements of 4 airline companies listed on the IDX in 2018-2021. The research sample was determined by specific criteria and obtained 16 observations for the financial statements of 4 companies for four years. Data analysis was done using a two-way ANOVA test using the Minitab 20 software. The results showed no differences in financial distress conditions calculated using the Altman, Grover, and Springer models. The conditions are not different because some of the same ratios are used as elements in the Altman, Grover, and Springate models. Three companies are always in distress for four consecutive years. Only one company experienced a healthy condition in 2018 and 2019 based on calculations using the three models. There are differences in financial distress conditions before and during the Covid-19 pandemic. The decline in financial performance during the 2020 and 2021 pandemic caused a decrease in the ratios used in the financial distress calculation model.